Instructional leadership strategies to strengthen teachers’ pedagogical practices in inclusive elementary schools: a case study from indonesia - Tanti Permata Sari; Muhammad Kristiawan; Azizatul Khairi (Jurnal Konseling dan Pendidikan, 2026)
The implementation of inclusive education requires teachers to develop adaptive pedagogical practices that respond to diverse student needs. However, the effectiveness of these practices was strongly influenced by the principal's instructional leadership. This study aimed to analyze the strategies used by principals to strengthen teachers' pedagogical practices in inclusive elementary schools. This study employed a qualitative approach with a case study design conducted at SD Alam Mahira in Bengkulu City, Indonesia. The participants consisted of the principal and teachers involved in inclusive learning. Data were collected through in-depth interviews, classroom observations, and document analysis. The data were analyzed using the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The findings indicated that principals implemented several strategic actions, including strengthening the vision of inclusive learning, developing teacher professional programs, conducting academic supervision and mentoring, optimizing school resources, and carrying out continuous evaluation through reflective discussions and professional learning communities. These strategies fostered a collaborative and supportive environment that enhanced teachers' pedagogical competence and encouraged the development of adaptive teaching practices. This study concluded that systematic and collaborative instructional leadership played a crucial role in improving teachers' pedagogical practices in inclusive education settings.